2002
DOI: 10.1182/blood.v99.2.680
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibitor of Janus tyrosine kinase 3, PNU156804, prolongs allograft survival and acts synergistically with cyclosporine but additively with rapamycin

Abstract: Janus kinase 3 (Jak3) is a cytoplasmic tyrosine (Tyr) kinase associated with the interleukin-2 (IL-2) receptor common gamma chain (␥ c ) that is activated by multiple T-cell growth factors (TCGFs) such as IL-2, -4, and -7. Using human T cells, it was found that a recently discovered variant of the undecylprodigiosin family of antibiotics, PNU156804, previously shown to inhibit IL-2-induced cell proliferation, also blocks IL-2-mediated Jak3 auto-tyrosine phosphorylation, activation of Jak3 substrates signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Hence Uckun and coworkers have demonstrated that administration of the rationally designed JAK3 inhibitor WHI-P-131/JANEX-1 attenuates acute GVHD in a fully mismatched mouse model (28). Using a chemically dissimilar JAK3 inhibitor, it was also found that allograft survival was significantly prolonged in a mouse model of heterotopic heart transplantation (29). Interestingly, JAK3 inhibition was effective in preventing diabetes in the NOD mouse (30).…”
Section: Discussionmentioning
confidence: 96%
“…Hence Uckun and coworkers have demonstrated that administration of the rationally designed JAK3 inhibitor WHI-P-131/JANEX-1 attenuates acute GVHD in a fully mismatched mouse model (28). Using a chemically dissimilar JAK3 inhibitor, it was also found that allograft survival was significantly prolonged in a mouse model of heterotopic heart transplantation (29). Interestingly, JAK3 inhibition was effective in preventing diabetes in the NOD mouse (30).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, small molecule inhibitors of STATs have not yet been successfully developed. However, relatively selective inhibitors of JAK kinases already exist, and inhibition of protein tyrosine kinases has been effective in animal models and in the clinic (39)(40)(41)(42). It will be interesting to determine the effects of JAK/STAT pathway inhibitors on inflammatory arthritis.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…PNU156804 blocks IL-2-dependent NF-kB and AP-1 activation 26 and it is a selective inhibitor of Janus tyrosine kinase 3 (Jak3). 27 Cycloprodigiosin also inhibits NF-kB activation, 21 although prodigiosin does not. 23 Taken together, these results suggest that inhibition of these signaling pathways cannot explain the apoptotic activity of prodigiosins in B and T lymphocytes.…”
Section: Prodigiosin Induces Apoptosis Of B-cll Cellsmentioning
confidence: 99%